Species richness and nest entrance characteristics of stingless bees (Hymenoptera: Apidae: Meliponini) in Ujung Kulon National Park, Banten, Indonesia - JAJANG MIHARJA; TRI ATMOWIDI; WINDRA PRIAWANDIPUTRA; DYAH PERWITASARI; SIH KAHONO (Society for Indonesian Biodiversity, 2024)
Abstract. Miharja J, Atmowidi T, Priawandiputra W, Perwitasari D, Kahono S. 2024. Species richness and nest entrance characteristics of stingless bees (Hymenoptera: Apidae: Meliponini) in Ujung Kulon National Park, Banten, Indonesia. Biodiversitas 25: 4961-4970. Stingless bees (Hymenoptera, Apidae, Meliponinae) are distributed in tropical and subtropical regions. Ujung Kulon National Park (UKNP), a conservation area of flora and fauna in the western part of Java, was designated by UNESCO in 1992 as a Natural World Heritage site. This study measured the species richness, nesting site, and nest-entrance characteristics of stingless bees in UKNP. Samplings of stingless bees were conducted by road sampling and based on the information from officers of UKNP and the local communities from June to December 2023. Results showed that 163 colonies of stingless bees were found belonging to four species, i,e., Tetragonula laeviceps, Tetragonula fuscobalteata, Heterotrigona itama, and Lepidotrigona terminata. Based on the number of colonies, L. terminata was the most dominant (44%), followed by T. laeviceps (41%), T. fuscobalteata (12%), and H. itama (3%), respectively. The nest of T. laeviceps was found in residential house cavities, bamboo and tree holes, and old and abandoned ant nests, showcasing their adaptability and resourcefulness. Meanwhile, the nest of T. fuscobalteata was found in the rock holes and tree cavities; L. terminata and H. itama nests were found in tree cavities. The unique nest entrance characteristics of each species further highlight their fascinating adaptability. This study showed a new distribution record of stingless bees in Ujung Kulon National Park, Banten, Indonesia.